Left supernumerary kidney: A rare case presentation - D.V. Krakhotkin, MD; V.A. Chernylovskyi, MD; D.N. Pikhovkin, MD; A.N. Ermolaev, MD, PhD; R.A. Bugaev (Radiology Case Reports, 2021)
The supernumerary kidney is an extremely rare, congenital renal anomaly and there are less than 100 cases reported in the current literature. This renal anomaly has its own collecting system, blood supply and well-defined encapsulated tissue. We report a case of left supernumerary kidney and solitary cyst of left native kidney in a 51-year-old man.